Argonaute2 promotes tumor metastasis by way of up‐regulating focal adhesion kinase expression in hepatocellular carcinoma12. Issue 5 (22nd April 2013) - Cheng, Na; Li, Yandong; Han, Ze‐Guang
Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers and shows a propensity to metastasize and infiltrate adjacent and more distant tissues. However, the mechanisms that contribute to tumor metastasis remain unclear. Here we evaluate the effect of Argonaute2 (Ago2), a member of the Ago gene family that plays a role in short interfering RNA‐mediated gene silencing, on HCC tumorigenesis, and metastasis. We found that Ago2 was frequently up‐regulated in HCC specimens compared to that in corresponding adjacent nontumor liver. Interestingly, Ago2 overexpression can promote proliferation, colony formation in an anchor‐independent manner, migration, tumorigenicity, and metastasis of HCC cells in vivo ; in contrast, Ago2 knockdown can restrict anchor‐independent colony formation, migration, and tumor metastasis of HCC cells in vivo . However, known microRNAs related to tumor metastasis appeared not be deregulated with Ago2 overexpression in HCC cells; even the knockdown of Dicer, which is responsible for microRNA biosynthesis, did not abolish the actions of Ago2 in HCC cells. Significantly, focal adhesion kinase (FAK), a well‐known molecule associated with tumor metastasis, was up‐regulated as a result of Ago2 overexpression. Chromatin immunoprecipitation assay showed that Ago2 can bind to the FAK promoter and then trigger its transcription. Moreover, an increased DNA copy number of Ago2 on chromosome 8q24, one of the most frequent DNA amplified regions, was validated and shown by way of fluorescence in situ hybridization. Conclusion : Our data demonstrate that Ago2 overexpression, as a result of genomic DNA amplification, promotes HCC tumorigenesis and metastasis by way of up‐regulation of FAK transcription, thereby providing new insight into HCC progression and Ago2 function. (HEPATOLOGY 2013)